PBL methodologies in simulated environments in vocational higher education: professional competences and learning processes - Pinheiro, Margarida Maria Solteiro Martins (2012)
This study reports a case study experience of a PBL (either as project-based learning or problem-based learning) methodology in simulated environments in vocational higher education. PBL was introduced to produce adaptable graduates whose professional competences are well attuned to the demands of a rapidly changing world. As main aspects of this development, we highlight the change from a teaching to a learning paradigm, the attention given to the social context of learning, the promotion of simulated environments of relevant real situations, the active responsibility of students for their own knowledge, and the global and interdisciplinary character of this knowledge. Given this outline, the empirical study assumes as its object the course of Projecto Profissional (Professional Project) in ISCA-UA (Higher Institute of Accounting and Administration of the University of Aveiro). It looks like that PBL-type methodologies in simulated environments add more value, essentially, at the beginning of the graduate’s professional career, but there were concerns about what it seems to be a gap between employers and other stakeholders regarding, especially, social, personal and learning competences. A key impediment to such engagement was the differences in perception of the type of competences truly valued by employers. We also found a difference in behavior between academics that do and do not have professional experience outside academia. Furthermore, PBL methodologies suggest the possibility of developing the entrepreneurial spirit of graduates and it is understood that the rehabilitation of students’ academic failure by feedback devices is important to this type of methodologies